VERTICES IN A SCALAR-GRAVITY SYSTEM IN THE TELEPARALLEL GRAVITY THEORY - Triyanta Triyanta; Kian Ming (INTEGRAL, 2013)
We consider a scalar field interacting gravitationally in teleparallel gravity theory. In this theory, the gravity is defined as a translational gauge field and thus gravita- tional interaction can be introduced through a minimal coupling prescription as in standard gauge theory. In this paper we consider scalar-gravity interacting terms of the scalar-gravity Lagrangian and derive the corresponding vertices by writing the tetrad field hμa as δaμ + bμa . We obtain six different vertices: one-gravity, two-gravity, etc. up to six-gravity vertices.Keywords: Teleparallel gravity, scalar eld, scalar-gravity vertices.Kami meninjau medan skalar yang berinteraksi secara gravitasional dalam teori gravitasi teleparalel. Dalam teori ini medan gravitasi didefinisikan sebagai medan gauge translasi sehingga interaksi gravitasi dapat dibangun melalui preskripsi ko- pling minimal sebagaimana dalam teori gauge standar. Dalam makalah ini kami meninjau suku-suku interaksi gravitasi skalar pada Lagrangian untuk sistem medan gravitasi skalar dan menurunkan verteks-verteks yang terkait melalui pengungkapan medan tetrad hμa sebagai δaμ + bμa . Kami peroleh enam verteks berbeda: verteks satu gravitasi, dua gravitasi, dan seterusnya sampai verteks enam gravitasi.Kata Kunci: Gravitasi teleparalel, medan skalar, verteks gravitasi skalar.